Integrasi Teknologi Dalam Pembelajaran IPA Kelas VI MI Tarbiyatul Athfal Gembong Pati - Nisa', Nurul Khoirun; Zafi, Ashif Az (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2024)
In the digital era, technology has become an inseparable part of human life. Technology offers many opportunities to improve various aspects of life, including the world of education. However, many teachers have not yet utilized technology in the learning process. This study aims to determine the implementation of technology integration in IPA learning in grade VI at MI Tarbiyatul Athfal Gembong Pati, and to evaluate the learning outcomes of students after the implementation of this technology. The approach used in this research is qualitative with a field research type. The results of the study show that: (1) In the implementation of technology integration in IPA learning in grade VI at MI Tarbiyatul Athfal Gembong Pati, teachers use video learning. The use of technology makes it easier for teachers to communicate information and increase students' awareness of the material being studied. (2) The integration of technology in IPA learning in grade VI MI Tarbiyatul Athfal Gembong Pati has a positive impact on student learning outcomes. The implementation of video learning as part of technology integration is proven to be effective in learning outcomes, as shown by students' better understanding and developing their various abilities in the cognitive, affective, and psychomotor domains.